The Relation Between Religiosity and Anxiety Levels in Adolescent Expectant Mothers - Alkhovian, Nida; Imansari, Bhekti; Rahayu, Hayinah (Journal of Health Sciences and Medical Development, 2024)
Adolescence is a very important period in human life because during this period there are changes both physically, mentally, socially, and emotionally. In pregnant women who are teenagers, it has a big influence on psychology, one of which is anxiety. There are several other factors, one of which is religiosity which can affect a person's self-quality in understanding and practicing his religious values so understanding of religion needs to be explored further so that it can reduce anxiety, especially in teenage pregnant women. This research method uses quantitative research with an emphasis on numerical analysis. which will be measured and processed through statistical analysis with correlational research to determine the strength or relationship between design variables. The research design is an analytical survey using a cross-sectional approach. using the religiosity questionnaire and the Hamilton Rating Scale for Anxiety (HARS). with the level of anxiety in teenage pregnant women in Kec. Kersamanah Kab. arrowroot So it is necessary to have counseling or health education for pregnant women so that the level of anxiety can be reduced and it is hoped that pregnant women will always think about it and do positive things so that it can help reduce anxiety.